2016
DOI: 10.18632/oncotarget.12129
|View full text |Cite
|
Sign up to set email alerts
|

TWIST1/miR-584/TUSC2 pathway induces resistance to apoptosis in thyroid cancer cells

Abstract: TWIST1, a transcription factor, plays a pivotal role in cancer initiation and progression. Anaplastic thyroid carcinoma (ATC) is one of the deadliest human malignancies; TWIST1 is overexpressed in ATC and increases thyroid cancer cell survival, migration and invasion. The molecular mechanisms underlying the effects of TWIST1 are partially known. Here, using miRNome profiling of papillary thyroid cancer cells (TPC-1) ectopically expressing TWIST1, we identified miR-584. We showed that TWIST1 directly binds miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 50 publications
1
25
0
Order By: Relevance
“…Additionally, miR-584 is an independent prognostic factor for the outcome in neuroblastoma patients (38). Downregulation of miR-584 was also observed in clear cell renal cell carcinoma (21), thyroid carcinoma (22,23) and glioma (24). These findings suggested that aberrant expression of miR-584 is a potential prognostic factor in these cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, miR-584 is an independent prognostic factor for the outcome in neuroblastoma patients (38). Downregulation of miR-584 was also observed in clear cell renal cell carcinoma (21), thyroid carcinoma (22,23) and glioma (24). These findings suggested that aberrant expression of miR-584 is a potential prognostic factor in these cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Ueno et al revealed that miR-584 overexpression decreased cell motility in clear cell renal cell carcinoma (21). Moreover, Orlandella et al showed that resumed expression of miR-584 inhibited the migration and invasion of thyroid carcinoma cells and induced their resistance to apoptosis (22,23). Wang et al indicated that miR-584 reexpression repressed cell groWTh, migration, invasion and vasculogenic mimicry of glioma (24,39,40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1A. TPC-1 is an established human PTC cell line [25, 26]. TPC-1 cells were cultured in FBS-containing complete medium, and were treated with different concentrations (10-1000 nM) of CZ415.…”
Section: Resultsmentioning
confidence: 99%